(untitled) - Vennard, John K. (New York, 1961)
Fluid mechanics is the study of fluids under all conditions of rest and motion. Its approach is analytical and mathematical rather than empricial; it is concerned with the basic printciples which allow the solution of the numerous and diversified problems encountered in many fields of engineering irrespective of the physical properties of the fluids involved
Keywords: Fluid mechanics,Cơ học chất lỏng